Development of Treasures Number Learning Media to Develop Early Childhood Numeracy Skills 4-5 Years Old - Siti Rokayah; Ferdian Utama; Leli Fertiliana Dea (Bulletin of Early Childhood, 2025)
This study aims to develop Number Treasure learning media made from plywood and test its effectiveness in improving numeracy skills of children aged 4-5 years at TK Arsya Bunda Bandar Mataram, Central Lampung. The research used Research and Development (R&D) method with 4D model (Define, Design, Develop, Disseminate). The subjects were 15 children aged 4-5 years. Data collection used observation, expert validation questionnaires, interviews, and documentation. Data analysis used quantitative techniques with Likert scale and qualitative descriptive. Media expert validation results obtained "Eligible" category and material expert "Eligible". Product trial showed significant improvement in children's numeracy skills, from 9 children (60%) in Undeveloped category to 10 children (67%) Developing as Expected and 3 children (20%) Developing Very Well. This media effectively trains five numeracy indicators: counting objects 1-10, understanding number concepts, recognizing number symbols, matching number symbols, and reciting numbers 1-10. Number Treasure media is a learning innovation that combines treasure hunt games with numeracy concepts using environmentally friendly plywood materials, easy to make, and attractive for early childhood.